2018
DOI: 10.1108/bepam-09-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

An implementation framework of value management in the Nigerian construction industry

Abstract: Purpose The purpose of this paper is to develop a framework for value management (VM) implementation by establishing the effect of critical success factors on current construction practices. This will aid stakeholders to improve productivity of construction practices in the Nigerian construction industry. The study established the requirements that ought to be satisfied for VM to successfully enhance productivity of construction activities. Design/methodology/approach Data collection was based on self-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 23 publications
4
49
0
Order By: Relevance
“…However, studies on the implementation of VM have focused on factors influencing the effective implementation of VM. Nevertheless, no study has measured or assessed the activities and elements that encourage the adoption of VM for sustainable building projects [91], particularly in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the implementation of VM have focused on factors influencing the effective implementation of VM. Nevertheless, no study has measured or assessed the activities and elements that encourage the adoption of VM for sustainable building projects [91], particularly in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Oke and Aghimien (2018) revealed that most Nigerian construction professionals are not oblivious of the benefits of adopting VM and the practicality of undertaking the methodology. Tanko et al (2018) also showed that the familiarity of the Nigerian construction professionals with VM is on average. With the knowledge of the Nigerian construction professionals in respect to VM methodology, one would think that the Nigerian construction industry would have fully embraced VM into its construction process.…”
Section: Introductionmentioning
confidence: 91%
“…The study additionally discovered that on-site learning is a huge factor influencing productivity of construction craft gangs. In a related study, Tanko et al [13] developed a framework for value management (VM) implementation, exploring the current construction practice factors that will improve construction productivity, the study found that people, environment, government and information are important factors that can be used by construction stakeholders to improve construction productivity practices in the Nigerian construction industry.…”
Section: Productivity Conceptsmentioning
confidence: 99%